Electrochemical sensors: a powerful tool in analytical chemistry - Stradiotto Nelson R.; Yamanaka Hideko; Zanoni Maria Valnice B. (Journal of the Brazilian Chemical Society, 2003)
Potentiometric, amperometric and conductometric electrochemical sensors have found a number of interesting applications in the areas of environmental, industrial, and clinical analyses. This review presents a general overview of the three main types of electrochemical sensors, describing fundamental aspects, developments and their contribution to the area of analytical chemistry, relating relevant aspects of the development of electrochemical sensors in Brazil.